Strategic Leadership Transformation in Indonesia’s Defense Policy: Responding to Non-Traditional Security Threats - Ary Mardi Wibowo; Guntur Eko Saputro; Bara Izzat Wiwah Handaru (Journal of Social Work and Science Education, 2027)
This study examines the transformation of strategic leadership within Indonesia’s national defense strategy in response to non-traditional security (NTS) threats, including cyber threats, disinformation, economic coercion, and gray-zone warfare. A Systematic Literature Review (SLR) was conducted, informed by PRISMA 2020 principles, drawing on Scopus and Google Scholar, and analyzed through thematic synthesis designed to surface convergences, contradictions, and paradoxes in the literature. Findings show that Indonesia’s leadership transformation has been real but asymmetric: doctrinal and integrative capacities have advanced through the Nusantara Trident Shield vision, the National Defense Council, and the recognition of cyberspace as a domain of warfare, while institutional and democratic-accountability capacities have lagged, most notably through the 2025 amendment to the TNI Law. Comparative evidence further suggests this risk stems less from military crisis involvement itself than from its open-ended, cross-institutional character. This study offers an integrative framework linking adaptive capacity, multidomain integration, digital capacity, and institutional capacity, positioning strategic leadership as a multidimensional process rather than a purely military or organizational construct. The framework provides a basis for strengthening cyber resilience, inter-agency coordination, and strategic intelligence, while binding any further military role expansion with sunset provisions and proportional civilian oversight. This study contributes theoretically by synthesizing conceptual and empirical developments on strategic leadership transformation and practically by offering guidance for developing adaptive, integrative, and democratically accountable defense policy in Indonesia.